Analisis Penyebab Kesulitan Belajar Mata KuliahStatistika Pada Mahasiswa Pendidikan Akuntansi Angkatan Tahun 2014Univesitas Muhammadiyah Surakarta - Nuryani, Devi Sagita, Drs. Djoko Suwandi, S.E, M.Pd (2017)
This research aims to determine: 1) The influence of earning motivation to learningdifficulties of students, 2) The Influence of the learning environment on student learning difficulties.. This descriptive study took place in FKIP Accounting Muhammadiyah University ofSurakarta. The entire student population is FKIP Accounting forces who are taking Statisticscourses, totaling 232 students. Samples taken as many as 146 students by random samplingtechnique. Data were obtained through documentation and questionnaires. The data analysistechnique used is multiple linear regression alysis, t-test, f, the relative contribution andeffective. The results of multiple linear regression analysis obtain the regression equation: Y =90,617 + 0,220X1 + 0,227X2. The conclusion is: 1) learning motivation significantly nfluence student learning difficulties. This is based on test t is known that from t = 2,886> t table = 1.977 atsignificance level of 5% with the Relative Contribution (SR) amounted to 51,72% and theeffective contribution (SE) 33,77%. 2) The learning environment is a significant effect on student learning difficulties. It is based on known bawha t test t = 3,835> t table = 1.977 at significancelevel of 5% with the Relative Contribution (SR) amounted to 48,28% and the ffectivecontribution (SE) 31,53%. 3) learning motivation, learning environment and talent together asignificant effect on student learning difficulties. This is based on test f note that Fhitung =61,552> F table = 3,06 at significance level of 5%. 4) The coefficient of determination (R2) of 0.653 indicates that the influence of motivation to learn, the learning environment and aptitudetowards learning difficulties is 65,3% while the rest influenced by other factors.